2012
DOI: 10.1089/gtmb.2012.0048
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perspectives on Genetic Testing for Psychiatric Disorders: The Attitudes of Veterans with Posttraumatic Stress Disorder and Their Families

Abstract: The perspectives of patients with posttraumatic stress disorder (PTSD) on genetic research have not yet been investigated in the genetics research literature. To provide a basis for research on attitudes toward genetic research in PTSD, we surveyed the U.S. Military Afghanistan/Iraq-era veterans with PTSD and their social support companions to investigate the attitudes and knowledge about genetics and genetic testing. One hundred forty-six veterans (76 with PTSD and 70 without PTSD) participated in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
0
9
1
Order By: Relevance
“…Randomized 16 participants. To recruit a target population for intervention study Other Brown, Strauss, et al, 2014 Compared 68 subjects with PTSD and 60 trauma-exposed non-PTSD controls. Purpose was to evaluate effects of study procedures involving exposure to aversive stimuli on participation distress. Part of recruitment study evaluating target population Dedert et al, 2012 Compared 76 veterans with PTSD and 70 without PTSD. Purpose was to evaluate attitudes toward genetic research in PTSD. Part of a 3-year longitudinal follow-up study …”
Section: Table A1mentioning
confidence: 99%
“…Randomized 16 participants. To recruit a target population for intervention study Other Brown, Strauss, et al, 2014 Compared 68 subjects with PTSD and 60 trauma-exposed non-PTSD controls. Purpose was to evaluate effects of study procedures involving exposure to aversive stimuli on participation distress. Part of recruitment study evaluating target population Dedert et al, 2012 Compared 76 veterans with PTSD and 70 without PTSD. Purpose was to evaluate attitudes toward genetic research in PTSD. Part of a 3-year longitudinal follow-up study …”
Section: Table A1mentioning
confidence: 99%
“…This may lead to an ambivalent view in the society towards genetic testing. PTSD patients are less ready to agree with genetic testing of their family members [ 188 ]. Furthermore, genetic poly- morphisms are differently distributed among the human populations on earth.…”
Section: Studies On Genetic Polymorphisms Among Military Personnelmentioning
confidence: 99%
“…Only one study to date has evaluated veterans’ attitudes toward psychiatric disorder genetic testing (7). This study found that veterans with posttraumatic stress disorder (PTSD) viewed genetic testing for PTSD less favorably than those without PTSD and were more likely to fear insurance discrimination.…”
Section: Introductionmentioning
confidence: 99%
“…A review of studies on general consumer attitudes surrounding genetic testing for psychiatric disorders identified several areas for future study: specifically, the need to study individuals without psychiatric disorders or not involved in genetics-related research, and the need for larger samples ( 2 ). Only one study to date has evaluated veterans’ attitudes toward psychiatric disorder genetic testing ( 7 ). This study found that veterans with posttraumatic stress disorder (PTSD) viewed genetic testing for PTSD less favorably than those without PTSD and were more likely to fear insurance discrimination.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation